The Influence of the OIDDE Learning Model on Virus Material on the Problem-Solving and Ethical Decision Making Ability of High School Students - Bintarawati, Eka; Hudha, Atok Miftachul; Husamah, Husamah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to analyze the effect of the OIDDE (Orientation, Identify, Discussion, Decision, and Engage in Behavior) learning model on virus material on students' problem-solving and ethical decision-making abilities in class X at SMAN 2 Sampit. The background of this study is based on the dominance of teacher-centered learning, which has not optimally developed students' higher-order thinking skills and ethical awareness. This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The sample consisted of 70 students, divided into an experimental class and a control class. Data were collected through problem-solving tests and ethical decision-making questionnaires and analyzed using descriptive and inferential statistics. The results showed that the experimental class achieved a higher mean posttest score in problem-solving ability (M = 87.00) compared to the control class (M = 73.86), with a significant difference (p < 0.05). The N-Gain score in the experimental class was 64.66% (moderate category), and the effect size was very large (Cohen’s d = 2.916). In terms of ethical decision-making, the experimental class also showed higher posttest scores (M = 90.49) than the control class (M = 85.66), with a significant difference (p = 0.012 < 0.05) and a very large effect size (Cohen’s d = 2.139). These findings suggest that the OIDDE learning model has a positive effect on improving students’ problem-solving and ethical decision-making abilities. However, further studies with larger samples are recommended to strengthen the generalizability of the results.